Analysis of Solvency Ratios and Profitability Ratios to Measure The Financial Performance of Aviation Sector Companies for The Period 2018 -2022 - Ali, Ahmad rayhan (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
This research aims to evaluate the solvency and profitability ratios of PT Garuda Indonesia Tbk and PT AirAsia Indonesia Tbk from 2018 to 2022, and their financial performance based on these ratios. The research method uses Solvency ratios, such as Debt to Assets Ratio (DAR) and Debt To Equity Ratio (DER), to measure a company's ability to manage debt against its assets and equity PT Garuda Indonesia Tbk and PT AirAsia Indonesia Tbk. The research results show that the financial performance of PT Garuda Indonesia Tbk and PT AirAsia Indonesia Tbk from 2018 to 2022 shows low solvency and profitability, based on industry standards. This evaluation provides important information for company management to improve debt management strategies, increase operational efficiency, and increase asset use to improve the company's long-term profitability.